Development and validation of a GEANT4 radiation transport code for CT dosimetry - Carver, DE (Health Phys, 2015)
We have created a radiation transport code using the GEANT4 Monte Carlo toolkit to simulate pediatric patients undergoing CT examinations. The focus of this paper is to validate our simulation with real-world physical dosimetry measurements using two independent techniques. Exposure measurements were made with a standard 100-mm CT pencil ionization chamber, and absorbed doses were also measured using optically stimulated luminescent (OSL) dosimeters. Measurements were made in air, a standard 16-cm acrylic head phantom, and a standard 32-cm acrylic body phantom. Physical dose measurements determined from the ionization chamber in air for 100 and 120 kVp beam energies were used to derive photon-fluence calibration factors. Both ion chamber and OSL measurement results provide useful comparisons in the validation of our Monte Carlo simulations. We found that simulated and measured CTDI values were within an overall average of 6% of each other.